PEMBUATAN MEDIA KOMIK PADA SUB MATERI METABOLISME KARBOHIDRAT UNTUK SISWA SMA KELAS XII - Rahmawati, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed to determine the validity of the comic in sub-matter of carbohydrate metabolism in class XII based onÂ  test results influence of the alcoholic beverages on the pancreatic organ histopathology and blood sugar levels of mice. This study uses a form research dan development. The comic media that has been developed is validated by seven validators, each validator validates the media with the physical aspect, designs and colors, images and text, as well as the validates material of the comic with the content aspect, suitability to the learning objectives, simplicity and elements of message design. The results showed that the average value of the content validity ratio from media validation that is 0,99 and the average value of the content validity ratio from validation of comic material that is 0,99. Based on the results of the study can be concluded that comics on the sub-matter of carbohydrate metabolism is feasible for use in learning class XII high school.Keywords: media, comic, carbohydrate metabolism, pancreas